Invisible Watermark based Image Authentication System with 5/3 Integer Wavelet Transform - Ghosh, Bibek Ranjan; Banerjee, Siddhartha; Sarkar, Deepro (International Journal of Computer Sciences and Engineering, 2022)
The authentication techniques deals with the originality of an object. It may be image, text, audio etc. Image authentication widely use watermarking techniques both in spatial and transform domain, especially discrete wavelet based techniques are preferred for features like multilevel analysis and lossless reconstruction. Again, integer wavelets has added advantage of generating only integer coefficients which further make computation simpler and faster. This work initially used forward 5/3 integer wavelet transform (IWT) on cover image to generate sub bands. A watermark image is taken and its SHA256 hash code is generated. The watermark and hash code are embedded in two different sub bands using dynamic random position map and the sub bands are inverse 5/3 IWT transformed to generate stego image. During extraction, the opposite process is adopted and the hash code of extracted watermark is computed and compared with original hash code for verification of authenticity. The experimental observation of the proposed method revealed around 61.5dB peak signal to noise ratio (PSNR), near zero mean square error (MSE) and very high structural similarity index measure (SSIM) with 8448 bit payload and PSNR 55 dB with 33024 bits of payload.